Optimal weighted data gathering in multi-hop heterogeneous sensor networks - Junlin Li; AlRegib, G. (MILCOM 2008 - 2008 IEEE Military Communications Conference, 2008)
We consider the problem of gathering data from an energy-limited wireless sensor network consisting of a set of sensor nodes and a sink node. Based on the heterogeneous nature of sensor networks, where data generated at different sensor nodes are of different fidelity and importance, we formulate the data gathering problem as maximizing the weighted sum of data generated at all sensors and turn it to a linear programming problem subject to the limited-energy constraints. Furthermore, we show that the optimal multi-hop routing for the weighted data gathering problem is character-based routing, where only ldquobadrdquo sensors relay data for ldquogoodrdquo sensors. An example application and simulation results are given to justify the proposed concept and algorithm.